2018
DOI: 10.1002/chem.201803637
|View full text |Cite
|
Sign up to set email alerts
|

Making Nanosized CHA Zeolites with Controlled Al Distribution for Optimizing Methanol‐to‐Olefin Performance

Abstract: From theoretical calculations and a rational synthesis methodology, it has been possible to prepare nanocrystalline (60-80 nm) chabazite with an optimized framework Al distribution that has a positive impact on its catalytic properties. This is exemplified for the methanol-to-olefin (MTO) process. The nanosized material with the predicted Al distribution maximizes the formation of the required MTO hydrocarbon pool intermediates, while better precluding excessive diffusion pathways that favor the rapid catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 19 publications
(18 reference statements)
6
51
0
1
Order By: Relevance
“…However, the AIMD simulations by Cnudde et al . showed that olefins can only diffuse through empty cavities, and we recently presented an optimized H‐SSZ‐13 catalyst with a controlled Al distribution that avoids the formation of HP intermediates in all the cavities, thus facilitating the product diffusion through the empty cages . These considerations, together with the clear differences in product distribution obtained from the beginning of the reaction for H‐SSZ‐13 and H‐SAPO‐34 (see Figure and S5‐S15) and the fact that they remain constant during the whole catalyst lifetime, support our proposal that selectivity is not mainly controlled by diffusion …”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…However, the AIMD simulations by Cnudde et al . showed that olefins can only diffuse through empty cavities, and we recently presented an optimized H‐SSZ‐13 catalyst with a controlled Al distribution that avoids the formation of HP intermediates in all the cavities, thus facilitating the product diffusion through the empty cages . These considerations, together with the clear differences in product distribution obtained from the beginning of the reaction for H‐SSZ‐13 and H‐SAPO‐34 (see Figure and S5‐S15) and the fact that they remain constant during the whole catalyst lifetime, support our proposal that selectivity is not mainly controlled by diffusion …”
Section: Methodsmentioning
confidence: 75%
“…In contrast, CHA‐type catalysts tend to produce more ethene and much less propene and butene, but there are differences in product distribution associated to framework composition. H‐SSZ‐13 always produces more ethene than propene, 45 % and 35 % respectively, while the opposite relationship is always found for H‐SAPO‐34 …”
Section: Methodsmentioning
confidence: 90%
“…First, different aluminosilicates as potential acid catalysts for the second CÀ C coupling step (MTO) were prepared. [41,42] Two zeolites with chabazite (CHA) structure and different acid contents (Si/Al = 15 and 30) were synthesized (see supporting information for synthesis details on all zeolites/zeotypes). A sample of benchmark SAPO-34, the commercial catalysts employed for this process, was also prepared.…”
Section: Structural and Physico-chemical Propertiesmentioning
confidence: 99%
“…The organization of objects, like molecules or clusters, in lowdimensionality nanosized structures is the key to attain materials endowed with new functionalities. [1][2][3][4] This leitmotiv in advanced material science often relies on spontaneous assembly mechanisms -such as molecular recognition or intermolecular interactions -which could be enhanced or accelerated by imparting proper external stimuli e.g. via electromagnetic fields, [5] chemical reagents, or by imposing geometric restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Moreover, the fine tuning of their pore architecture and their hydrophilic/hydrophobic character can improve their performance for technological or industrial applications. [4,[16][17][18][19][20][21][22][23][24] The geometrical constraints of the zeolitic framework can be proficiently exploited to induce the formation of nanostructured arrays with the desired dimensionality. Supramolecular materials which do not require chemical reactions to form compositessuch as dye-zeolite composites/artificial antenna systems in zeolite channels, [25][26][27][28][29][30][31][32][33] biomolecules and chromophores immobilized in 1-D channels, [34][35][36][37][38][39][40][41] or low-dimensional nanoarchitectures of molecular clusters [42][43][44] -have been successfully realized.…”
Section: Introductionmentioning
confidence: 99%